2023
DOI: 10.3390/pathogens12040602
|View full text |Cite
|
Sign up to set email alerts
|

Increased Clinical Signs and Mortality in IFNAR(−/−) Mice Immunised with the Bluetongue Virus Outer-Capsid Proteins VP2 or VP5, after Challenge with an Attenuated Heterologous Serotype

Abstract: Bluetongue is an economically important disease of domesticated and wild ruminants caused by bluetongue virus (BTV). There are at least 36 different serotypes of BTV (the identity of which is determined by its outer-capsid protein VP2), most of which are transmitted by Culicoides biting midges. IFNAR(−/−) mice immunised with plant-expressed outer-capsid protein VP2 (rVP2) of BTV serotypes -1, -4 or -8, or the smaller outer-capsid protein rVP5 of BTV-10, or mock-immunised with PBS, were subsequently challenged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Globally speaking, the absence of detectable KEMV RNA in the older males’ hearts and the higher Ct values in the other tested organs of these older males strongly suggest an intriguing lower susceptibility of these animals. We have previously shown that attenuation of virulence of a BTV generated by reverse genetics correlated with lower levels of replication in IFNAR (−/−) mice, as observed by higher Ct values, regardless of the sex of the mice [ 22 ]. The Ct values of mice inoculated with KEMV Ps.BSR30 clearly indicate that there was an attenuation of virulence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally speaking, the absence of detectable KEMV RNA in the older males’ hearts and the higher Ct values in the other tested organs of these older males strongly suggest an intriguing lower susceptibility of these animals. We have previously shown that attenuation of virulence of a BTV generated by reverse genetics correlated with lower levels of replication in IFNAR (−/−) mice, as observed by higher Ct values, regardless of the sex of the mice [ 22 ]. The Ct values of mice inoculated with KEMV Ps.BSR30 clearly indicate that there was an attenuation of virulence.…”
Section: Resultsmentioning
confidence: 99%
“…Vertrel XF (Sigma-Aldrich, Saint-Quentin-Fallavier, France) is an organic solvent that facilitates freeing orbivirus particles from interaction with cell debris [ 22 , 34 ]. On day 6 post-infection, BSR cell lysates, including cell debris and culture supernatants, were collected.…”
Section: Methodsmentioning
confidence: 99%
“…We initially assessed the virulence of our BTV-1RG C7 using 10, 100 or 1000 pfu/mouse in 3 groups of 5 IFNAR (-/-) mice. Although clinical signs were observed by day 4, all mice recovered by day 6–7 [ 51 ], showing that BTV-1RG C7 is not as virulent as other BTV strains tested in this model [ 36 , 47 , 48 ]. Two groups of 5 IFNAR (-/-) mice each were used to compare the effects of infection with either BTV-1RG C7 or BTV-1∆NS4.…”
Section: Methodsmentioning
confidence: 99%
“…Bluetongue virus (BTV) belongs to the Orbivirus genus of the Reoviridae family, characterized by a double-stranded RNA genome with 10 segments coding for various proteins. Currently, at least 36 different BTV serotypes are circulating worldwide [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%